Speech Comprehension and Its Relation to Other Auditory Parameters in Elderly Patients With Tinnitus - Bureš, Zbyněk; Profant, Oliver; Svobodová, Veronika; Tóthová, Diana; Vencovský, Václav; Syka, Josef (Frontiers in Aging Neuroscience, 2019)
Deteriorated speech comprehension is a common manifestation of the age-related decline of auditory functions (presbycusis). It could be assumed that when presbycusis is accompanied by tinnitus, general hearing functions, and particularly comprehension of speech in quiet and speech in noise, will be significantly affected. In this study, speech comprehension ability and other parameters of auditory function were assessed in elderly subjects with (T, n=25) and without (NT, n=26) tinnitus, aiming for examination of both peripheral and central auditory processing, Apart from high-frequency audiograms in quiet and in background noise, speech recognition thresholds in silence or in competitive babble noise, and the ability to understand temporally gated speech, we measured also sensitivity to frequency modulation and interaural delay, gap detection thresholds, or the difference limens of intensity. The results show that in elderly participants matched by age (mean ages around 68 years), cognitive status (median MoCA scores around 27), and hearing thresholds (median pure-tone averages around 16 dB HL), tinnitus per se has little influence on speech comprehension. The tinnitus patients also show similar gap-detection thresholds, sensitivity to interaural intensity difference, and sensitivity to frequency modulation as the NT subjects. Despite these similarities, nevertheless, significant differences in auditory processing have been found in the tinnitus participants: a worse ability to detect tones in noise, a higher sensitivity to intensity changes, and a higher sensitivity to interaural time differences. Additional correlation analyses further revealed that speech comprehension in the T subjects is dependent on the sensitivity to temporal modulation and interaural time delay, while these correlations are weak and non-significant in the NT subjects. Therefore, despite similarities in average speech comprehension and several other parameters of auditory function, elderly people with tinnitus exhibit different auditory processing, particularly at suprathreshold level. The results also suggest that speech comprehension ability of elderly tinnitus patients relies more on temporal features of the sound stimuli, especially under difficult conditions, compared to elderly people without tinnitus.